PENERAPAN TEKNOLOGI INFORMASI DALAM SISTEM MANAJEMEN INFORMASI UNTUK MENINGKATKAN DAYA SAING PERUSAHAAN - Dede Rusmana; Franciskus Antonius Alijoyo (OIKOS: Jurnal Kajian Pendidikan Ekonomi dan Ilmu Ekonomi, 2025)
In this digital era, information technology (IT) has become a key factor in increasing company competitiveness. Proper implementation of IT in information management systems can help companies to increase efficiency, effectiveness and productivity. This research aims to explore the application of information technology in information management systems and how this can increase company competitiveness. This study used qualitative research methods. The data collection technique in this research is literature study. The data that has been collected is then analyzed in three stages, namely data reduction, data presentation and drawing conclusions. The research results show that the application of IT in information management systems can increase a company's competitiveness. Companies need to pay attention to the factors that influence the success of implementing IT in information management systems in order to achieve optimal results, including management support, availability of IT infrastructure, staff skills and knowledge, communication and coordination.